Odpowiedzialność administracyjna na obszarach specjalnych o charakterze przyrodniczym. Zagadnienia wybrane - Stelmasiak, Jerzy (Studia Prawnoustrojowe, 2019)
Administrative responsibility in special areas of natural character must take into account a special legal regime in the form of prohibitions in force on their territory. This applies to every entity using the natural environment inthese special areas. In addition, the above prohibitions are introduced in order to protect, in particular, exceptional natural values and landscape values by means of an appropriate form of nature protection, for example landscape park or protected landscape area. Therefore, an entity using the natural environment will bear administrative responsibility both if it breaches common prohibitions as well as prohibitions or restrictions related to the creation of an area form of nature protection. This also applies to restrictions in running an economic activity or even prohibiting it when it would threaten the proper functioning of a special area of natural character. In addition, it may also be banned to construct new building facilities in a 100-meter wide strip of land from the banks of rivers or lakes. This means that construction of a building facility in this area is treated as an unauthorized construction, which is subject to a demolition order, i.e. it can not be legalized in any case.